Some Problems with Reciprocity - Algazi, Gadi (ENDOXA, 2002)
The author rejects an mechanical application of reciprocity for analysing social relations, both in past and current contexts. As the norm of reciprocity is ojien invoked by the actors themselves, the research can reproduce actors’ interested representations oftheir relations. The paper indicates some of the problems involved.